Solidarity and care as relational practices - Jennings, Bruce (Bioethics, 2018)
Many working in bioethics today are engaging in forms of normative interpretation concerning the meaningful contexts of relational agency and institutional structures of power. Using the framework of relational bioethics, this article focuses on two significant social practices that are significant for health policy and public health: the practices of solidarity and the practices of care. The main argument is that the affirming recognition of, and caring attention paid to, persons as moral subjects can politically motivate a society in three respects. The recognition of solidarity and the attention of care can prompt progressive change toward a democratic willingness: (a) to provide for equal respect for rights and dignity; (b) to provide the social resources and services needed for just health and well‐being; and (c) to focus its creativity and wealth on the actualization of potential flourishing of each and all. Solidarity is discussed as a morally developmental stance that moves from standing up for another, standing up with another, and standing up as another. Care is discussed as a morally developmental stance that moves from the attentive rehabilitation of another, attentive companionship with and for another, and attentive commitment to another.